2014
DOI: 10.1111/1556-4029.12468
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Vertebrate Scavenging Behavior in a Northwest European Woodland Context

Abstract: Vertebrate scavengers can modify surface deposited human remains which can hinder forensic investigations. The effects of such scavenging vary between species and regions. Published research into the effects of the scavenging of human remains is dominated by work from North America with few studies covering Northwestern Europe. Forensic scientists, investigators, and police search officers in Northwestern Europe are often left questioning on a basic level as to which scavengers are active and how they might af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 69 publications
0
60
0
Order By: Relevance
“…Within northwest Europe and specifically within Britain, the red fox ( Vulpes vulpes ) and the Eurasian Badger ( Meles meles ), henceforth referred to as fox and badger within this paper, are the most common wild scavengers which have the potential to rapidly modify and disperse a set of remains through scavenging and disarticulation. Avian scavengers, such as carrion crow ( Corvus corone ) and buzzard ( Buteo buteo ), are also common scavengers in this region . However, they disperse remains to a lesser extent than foxes and badgers, as well as produce a different pattern of modification through scavenging .…”
mentioning
confidence: 99%
“…Within northwest Europe and specifically within Britain, the red fox ( Vulpes vulpes ) and the Eurasian Badger ( Meles meles ), henceforth referred to as fox and badger within this paper, are the most common wild scavengers which have the potential to rapidly modify and disperse a set of remains through scavenging and disarticulation. Avian scavengers, such as carrion crow ( Corvus corone ) and buzzard ( Buteo buteo ), are also common scavengers in this region . However, they disperse remains to a lesser extent than foxes and badgers, as well as produce a different pattern of modification through scavenging .…”
mentioning
confidence: 99%
“…However, it is possible to utilize deer as animal analogues in forensic studies seeking to recreate outdoor crime scene scenarios in the U.K. because deer are wildlife and do not present a risk in the spread of disease to domestic livestock (42). Previous studies using deer as human proxies did show some similarities in the scavenging behavior and patterns of different scavenger species toward deer and human remains (10,11,43).…”
Section: Methodsmentioning
confidence: 92%
“…Nevertheless, Young et al. indicated that remains initially deposited as fresh can be further scavenged and modified when skeletonized, so it is important to also analyze bite marks produced on dry bones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations